THE MEANING OF PERFORMATIVE VERBS IN ENGLISH MOVIES - Rosaria Mita Amalia (Elite : English and Literature Journal, 2019)
The utterance that contains performative verb explicitly has subject pronominal I, present simple tense, and direct object. The meaning of performative verb contains declarative, representative/assertive, expressive, directive, and commisive meaning.The method used in this research is a descriptive method. According to Djajasudarma (1993 : 8), a descriptive method aims to make descriptions; make pictures, paint  a systematic, factual and accurate picture of the information or data, properties, and phenomena under study. The steps of this research were: (1) literature review, (2) the collection of data, (3) data analysis, and (4) conclusions.The data was taken from conversation on ‘Gladiator’ and ‘A Few Good Man’ Movies. The results show that the performative verbs in the movies are ‘warn’, ‘assume’, ‘admit’ which are categorized into representative/assertive meaning, ‘promise’, ‘bet’, ‘reject’, ‘swear’ whose meanings are commisive,’order’, ‘ask’, ‘advise’, ‘beg’, ‘command’ which have directive meaning, ‘judge’, ‘announce’, ‘declare’ which have declarative meaning, and ‘apologize’, ‘thank’, ‘honor’, ‘salute’ which have expressive meaning. All performative verbs mentioned are found in explicit and implicit performative speech. Keywords: Performative verb, assertive, directive, declarative, commisive, and expressive meaning ABSTRAK Ucapan yang mengandung verba performatif secara eksplisit memiliki ciri; subjek pronominal I,  dalam bentuk present simple tense, dan direct object. Arti verba performatif mengandung makna deklaratif, representatif / asertif, ekspresif, direktif, dan komisif. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Menurut Djajasudarma (1993: 8), metode deskriptif bertujuan untuk membuat deskripsi; membuat gambar, melukiskan gambaran sistematis dari informasi atau data, sifat, dan fenomena yang diteliti Langkah-langkah penelitian ini adalah: (1) tinjauan literatur, (2) pengumpulan data, (3) analisis data, dan (4) kesimpulan. Data diambil dari percakapan para tokoh dalam film 'Gladiator' dan 'A Few Good Men'. Konversasi yang terjadi dalam film merupakan refleksi terhadap konversasi yang sebenarnya dalam kehidupan sehari-hari. Data yang berhasil dihimpun dari kedua film di atas sangatlah cukup dan valid sebagai represntasi penggunaan verba performatif dalam kehidupan. Hasil penelitian menunjukkan bahwa verba performatif yang ditemukan dalam film-film tersebut adalah warn’, ‘assume’, ‘admit’ yang dikategorikan menjadi makna asertif, ‘promise’, ‘bet’, ‘reject’, ‘swear’ termasuk dalam makna komisif. Selanjutnya adalah verba ’order’, ‘ask’, ‘advise’, ‘beg’, ‘command’ yang termasuk ke dalam kategori direktif. Lalu untuk kategori makna deklaratif ditemukan dalam verba seperti ‘judge’, ‘announce’, ‘declare’, dan verba ‘apologize’, ‘thank’, ‘honor’, ‘salute’ yang memiliki makna ekspresif.Semua verba performatif yang disebutkan ditemukan dalam tindak tutur performatif eksplisit dan implisit. Kata kunci: verba performatif, makna asertif, direktif, deklaratif, komisi, dan ekspresif